Comparative measurements of the energy consumption of 51 electric, hybrid and internal combustion engine vehicles - Howey, D; Martinez-Botas, R; Cussons, B; Lytton, L (Elsevier, 2011)
This paper presents the measured energy consumption results of a range of efficient vehicles over a 57 miles urban/extra-urban route. The results show that on average the electric vehicles used the least amount of energy (average 0.62 MJ/km), followed by the hybrid vehicles (average 1.14 MJ/km), and the internal combustion engine vehicles (average 1.68 MJ/km). The hydrogen fuel cell vehicle used 1.2 MJ/km. An estimate of CO₂ emissions was also made and it was found that hybrids gave the lowest CO₂ emissions, with around half of the vehicles emitting less than 70 gCO₂/km. The most efficient diesel combustion engine vehicles emitted about 80 gCO₂/km but the majority exceeded 110 gCO₂/km. The majority of electic vehicles emitted 70-110 gCO₂/km assuming a United Kingdom grid average emissions factor of 542 gCO₂/kWh.